Assessing Mother Plant Age Impact on Apical Cutting Production and Field Performance - Nyawade, S.; Parker, M. (International Potato Center, 2024)
An experiment was conducted at Stockman Rozen Kenya Ltd to evaluate the effects of mother plant physiological age on production and field performance of apical cuttings. Original tissue culture plantlets (10 replicates) of cvs. Shangi, Wanjiku, Unica and Taurus were grown in potted media under greenhouse conditions. The first cut from each replicate was used to make submothers, which together with the original tissue culture (TC) mothers were used as stock mothers to produce apical cuttings. The stock mothers were evaluated for the maximum number of cuttings a single stock can produce over different rounds or age of cut. A round (or shoot age) refers to the time elapsed between stock planting and the time cuttings were harvested from the subsequent regrowth. The stock mothers were kept in a juvenile stage to acquire shoot cuttings, maximizing their vegetative growth. The apical cuttings from the same stock at different rounds of cut were hardened and grown in the field, 20 plants per cultivar per round. Tuber yield from each round (both numbers and weights) was assessed from 4 sequential harvests taken at weeks 5, 7, 9 and 11-: four plants per harvest. All the cultivars produced observably more cuttings in successive cuts up to the 7th round, with exception of Taurus which was clearly the least producer.